Optical components, systems, and measurement techniques / Rajpal S. Sirohi, Mahendra P. Kothiyal - Sirohi, Rajpal S. (Optical engineering (Marcel Dekker, Inc.), 1991)
Presents optical techniques and measurement procedures, providing basic background information on optics and lasers, their components and basic systems.